PERAN KEPALA SEKOLAH DALAM MENNGKATKAN MUTU PENDIDIKAN PADA SITUASI PANDEMI DI SMP NEGERI 9 MALANG - Nuruddin Muzakki; Maskuri Maskuri; Dian Mohammad Hakim (VICRATINA, 2021)
This study aims to analyze and describe the role of school principals in improving the quality of education in a pandemic situation. because the quality of education is a major benchmark that must be met by school principals, even more so in the current pandemic situation. The quality of education can be achieved with the results of joint efforts with education actors, but the role of the principal also has a significant impact on changes, especially in providing changes to the quality of education in schools. The role of the principal is the main element in planning, carrying out the process, and achieving the results to be achieved at the specified quality standards to support the improvement of the quality of education.